A new telemetry system for measuring the rotating ring's temperature in a tribological test rig for mechanical face seals. (February 2017) - Valigi, Maria Cristina; Braccesi, Claudio; Logozzo, Silvia; Conti, Lorenzo; Borasso, Massimiliano
Abstract: This paper presents the development, installation and application of a new wireless telemetry system for measuring the rotating ring's temperature of mechanical face seals. This new thermometric chain has been integrated in a preexisting tribological test rig, used in laboratory to characterize the dynamic, acoustic and thermal behavior of mechanical face seals. Before use, the new telemetry system has been subjected to calibration, validation as well as mechanical and electrical verification. Furthermore, the measuring uncertainty of the thermometric chain has been evaluated according to the Guide to the expression of uncertainty in measurement. Highlights: We provide a brief review of the prior tribological test rigs for measuring the temperature of a mechanical face seals. A wireless thermometric chain for measuring the rotating ring's temperature is developed, calibrated and validated. We present the results of some experimental campaigns.